PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS KARTU SOAL DENGAN PENDEKATAN KONSTRUTIVISTIK PADA MAHASISWA PGSD STKIP MELAWI - Samsul Bahri, Fransisco Adam Yuli Budhiarti (Jurnal Pembelajaran Prospektif, 2020)
Development research is research that produces a new product, in the form of concepts, theories, models, methods, strategies, and media in a learning process. The product is expected to provide benefits both theoretically and practically in improving the quality of learning. This study aims to determine the effectiveness of the card-based learning model with constructivist approaches in improving learning outcomes and learning activeness. The study used an experimental method of one group pretest-posttest design with descriptive qualitative and quantitative narrative approaches. Procedural development model consisting of; potential and problems, data collection, productdesign, validation and revision, testing and final products. Data collection techniques and instruments used observation and test techniques with observation sheet instruments and question exercises (pretest-posttest). Analysis of qualitative and quantitative descriptive narrative data. The results of data analysis found 40% of students with a difference in learning outcomes after actions above 10 points, 46.66% difference in learning outcomes below 10 points, 6.66% stagnant, and 6.66% decreased. While the activeness of learning before the action is 33.33% and 66.66% after the action. This means that learning outcomes and activeness increase significantly from  the previous condition. So it can be concluded that the card-based learning model witha constructivist approach can improve learning outcomes and student learningactiveness.